Assumptions and deeming. Issue 2 (29th April 2014) - D. Francis, Ronald
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to analyse and provide a framework for considering assumptions. Design/methodology/approach – This paper is a conceptual study. Findings – This paper provides both an analysis of assumptions and also a prescription for recognising and dealing with assumptions. Research limitations/implications – As the paper is a conceptual analysis, the research implications are not relevant. Practical implications – The analysis provided in this article should be of help to those working in financial crime and also have a wider application. Originality/value – Except where due acknowledgement is given, to the best of the author's knowledge, this paper is quite original.